2017
DOI: 10.29252/ijrm.15.12.757
|View full text |Cite
|
Sign up to set email alerts
|

In vitro fertilization outcome in frozen versus fresh embryo transfer in women with elevated progesterone level on the day of HCG injection: An RCT

Abstract: Background:The effect of elevated progesterone level on human chorionic gonadotropin (HCG) day in in vitro fertilization cycles is controversial. Some suppose that rise in progesterone level seems to have a negative impact on implantation and pregnancy by desynchronizing the endometrium, while others disagree.Objective:To evaluate the superiority of the frozen cycle over fresh cycle on live birth in patients with elevated progesterone level on HCG day.Materials and Methods:In this double-blind, randomized clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 12 publications
0
5
0
1
Order By: Relevance
“…The finding that the ‘freeze-all’ strategy resulted in a similar cumulative live birth rate among high responders compared with the ‘fresh-transfer’ strategy is consistent with previous RCTs. The nine RCTs that have evaluated the live birth rate following a ‘freeze-all’ strategy compared with a ‘fresh-transfer’ strategy were all performed in normal or high responders where the minimum average number of oocytes retrieved was 12 in both groups (Ferraretti et al , 1999; Shapiro et al , 2011a,b; Chen et al , 2016; Aghahosseini et al , 2017; Coates et al , 2017; Aflatoonian et al , 2018; Shi et al , 2018; Vuong et al , 2018). A recent systematic review and meta-analysis based on five of these RCTs reporting cumulative live birth rate (Ferraretti et al , 1999; Shapiro et al , 2011a,b; Chen et al , 2016; Vuong et al , 2018) showed no differences in cumulative live birth rates between the ‘freeze-all’ and ‘fresh-transfer’ strategies (risk ratio 1.04, 95% CI 0.97–1.11) (Roque et al , 2018b).…”
Section: Discussionmentioning
confidence: 99%
“…The finding that the ‘freeze-all’ strategy resulted in a similar cumulative live birth rate among high responders compared with the ‘fresh-transfer’ strategy is consistent with previous RCTs. The nine RCTs that have evaluated the live birth rate following a ‘freeze-all’ strategy compared with a ‘fresh-transfer’ strategy were all performed in normal or high responders where the minimum average number of oocytes retrieved was 12 in both groups (Ferraretti et al , 1999; Shapiro et al , 2011a,b; Chen et al , 2016; Aghahosseini et al , 2017; Coates et al , 2017; Aflatoonian et al , 2018; Shi et al , 2018; Vuong et al , 2018). A recent systematic review and meta-analysis based on five of these RCTs reporting cumulative live birth rate (Ferraretti et al , 1999; Shapiro et al , 2011a,b; Chen et al , 2016; Vuong et al , 2018) showed no differences in cumulative live birth rates between the ‘freeze-all’ and ‘fresh-transfer’ strategies (risk ratio 1.04, 95% CI 0.97–1.11) (Roque et al , 2018b).…”
Section: Discussionmentioning
confidence: 99%
“…Our study is the first to compare the freeze-all strategy to fresh ET into the aforementioned subgroups. Evaluating the freeze-all strategy in all of these subgroups from poor to hyper-responders is important, as all the RCTs available for evaluating the LBR following the freeze-all strategy were performed in normal and high responders with a minimum mean number of retrieved oocytes of 12 ( Chen et al ., 2016 ; Shapiro et al ., 2011a ; b ; Shi et al ., 2018 ; Vuong et al ., 2018 ; Wei et al ., 2019 ; Coates et al ., 2017 ; Ferraretti et al ., 1999 ; Aghahosseini et al ., 2017 ; Aflatoonian et al ., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Editorials published in 2013 proposed that eFET would become accepted as the gold standard practice in IVF (19,20), although the evidence to support this claim at that time was based mostly on pooled observational data and only limited data from randomized trials. More studies have been conducted recently, and to date, 11 randomized controlled trials comparing eFET and fresh ET have been published (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31).…”
Section: Cryopreservation Todaymentioning
confidence: 99%